Marker Assisted Selection in Rice - Wani1, K. A. Bhat1, S. Chalkoo2, M. R. Mir3 and Shabir. A. Wani4, Sabina Akhtar1*, M. A. Bhat1, Shafiq. A. (Journal of Phytology, 2010)
A rising global population requires increased crop production and some research suggests that the rate of increase in crop yields is currently declining and traits related to yield, stability and sustainability should be a major focus of plant breeding efforts. These traits include durable disease resistance, abiotic stress tolerance and nutrient and water use efficiency. The use of DNA markers in plant breeding is called marker assisted selection (MAS). So far, about 40 major blast genes have been identified, about 30 genes have been mapped on different rice chromosomes, and tightly linked DNA markers have been developed. Eight blast resistance genes have been cloned and the genes have been used for their selective introgression into susceptible rice cultivars. Recently Genetic and physical mapping of blast resistance gene Pi-42(t) located on the short arm of rice chromosome 12 in a resistant genotype ‘DHR9’ has been achieved. The PCR-based allele specific and in Del marker sets are available for nine blast resistance genes and they provide an efficient marker system for MAS for blast resistance breeding. Recently a novel resistance gene Pi40 derived from wild Oryza species (O. australiensis), have been located on chromosomes 6 and it shows promise for broad spectrum resistance. Tetep, the likely donor of Pi5(t) confers broad-spectrum resistance to Magnaporthe grisea. Additionally, several blast resistance genes could be combined using MAS in a single genetic background to develop rice cultivars with broad-spectrum durable resistance to blast. In future combination of conventional and marker assisted selection approach will provide opportunities for breeders to develop high yielding, stress tolerant and better quality rice cultivars. No doubt the cost of using DNA markers is expensive but it is worth the investment. Key words: Rice, Molecular markers, Polymorphism, Foreground and background selection <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Sabina Akhtar et al. Marker Assisted Selection in Rice. J Phytol 2/10 (2010) 66-81